Analysis Of Mathematical Critical Thinking Skills In Terms Of Gender In Class VIII Material of Cube - Rosmaiyadi Rosmaiyadi; Buyung Buyung; Sri Hartianingsih (JPMI (Jurnal Pendidikan Matematika Indonesia), 2023)
This study aims to describe mathematical critical thinking skills in terms of gender and determine the factors that influence student errors in completing mathematical critical thinking skills in the Cube material for class VIII MTs Negeri 1 Singkawang. The research method used is descriptive qualitative method. The subjects of this study were 30 students in class XI MTs Negeri 1 Singkawang. Data collection using an instrument in the form of a mathematical critical thinking ability test in the form of a description test that is adapted to mathematical critical thinking skills. The data analysis technique was carried out with steps of data validity, data reduction, data presentation, as well as verification and conclusion. The results showed that: 1) The mathematical critical thinking ability of male students on the Cube material was included in the low category, while the mathematical Critical Thinking ability of female students on the Cube material was included in the medium category; 2) the factors that cause male and female students' errors are the same in solving mathematical critical thinking skills in terms of gender in the Cube material for class VIII MTs Negeri 1 Singkawang, namely internal factors and cognitive factors.